Carbonate reservoirs : porosity and diagenesis in a sequence stratigraphic framework - Moore, Clyde H. (Developments in sedimentology ;, 2013)
The 2nd Edition of Carbonate Reservoirs aims to educate graduate students and industry professionals on the complexities of porosity evolution in carbonate reservoirs. In the intervening 12 years since the first edition, there have been numerous studies of value published that need to be recognized and incorporated in the topics discussed. A chapter on the impact of global tectonics and biological evolution on the carbonate system has been added to emphasize the effects of global earth processes and the changing nature of life on earth through Phanerozoic time on all aspec.